Lubrication mechanisms of C‐MoS2‐Fe2O3 (Fe3O4) nano‐composite lubricants at the rubbing interfaces of non‐copper coated solid wires against the contact tube. Issue 1 (15th January 2019) - Li, Z.X.; Wan, Q.; Li, G.D.; Li, H.; Li, H.J.; Zhang, T.L.; Kim, H.J.; Tillmann, W.
Abstract: Graphite‐MoS2 ‐Fe2 O3 (Fe3 O4 ) nano‐composite lubricating coatings were prepared on the surfaces of non‐copper coated solid wires by a mechanical coating technique. The tribological behaviours of graphite‐MoS2 ‐Fe2 O3 (Fe3 O4 ) coatings at the rubbing interfaces of welding wires against the contact tube were investigated. The results demonstrate that the lubricating properties of graphite‐Fe3 O4 coatings outperform the lubricating properties of graphite‐Fe2 O3 coatings. The anti‐wear performance of the contact tube is strengthened with increasing nano‐MoS2 contents. Layers of protective tribofilms are formed at the rubbing interfaces of welding wires against a contact tube by tribochemical reaction among lubricants. The tribofilms are composed of FeO, MoO3 and FeMoO4 with excellent lubricating properties. They can avoid direct contact of welding wires against the contact tube, thus decreasing contact tube wear. With the transition of the contact tube wear from mild to severe, the dominant wear mechanisms of contact tube change from fatigue peeling and oxidative wear to abrasive wear and arc ablation.